Sounds and perception new philosophical essays - Nudds, Matthew; O'Callaghan, Casey (Oxford : Oxford University Press, 2009)
'Sounds and Perception' examines auditory perception and the nature of sounds, an emerging area of interest in the philosophy of mind & perception, & in the metaphysics of sensible qualities. The individual essays discuss a wide range of issues including the nature of sound & the spatial aspects of auditory experience.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Auditory perception; Sounds